Hyaluronic acid/EDC/NHS-crosslinked green electrospun silk fibroin nanofibrous scaffolds for tissue engineering. Issue 102 (19th October 2016) - Yang, Xingxing; Wang, Xiaoyun; Yu, Fan; Ma, Linlin; Pan, Xiaohan; Luo, Gejie; Lin, Si; Mo, Xiumei; He, Chuanglong; Wang, Hongsheng
Abstract : The mechanical properties of SF nanofibrous matrices were enhanced through crosslinking with HA/EDC/NHS for soft tissue engineering. Abstract : Regenerated silk fibroin (SF) from Bombyx mori was used widely in biomedical fields due to its excellent properties. In recent years, green electrospun SF nanofibers have attracted much attention from researchers due to their good biosafety and environmentally friendly nature. However, the mechanical properties of SF nanofibers are unsatisfactory, which greatly restricts the application of SF in tissue engineering. In this study, the tensile performance of the green electrospun SF nanofibers was significantly improved through a simple and eco-friendly process of hyaluronic acid (HA)/1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC)/ N -hydroxysuccinimide (NHS)-crosslinking. Our data showed that the strain performance of the HA/EDC/NHS-crosslinked SF nanofibrous matrices was dramatically improved up to 120%, and was much better than that of the conventionally treated ones (ethanol soaking or fumigating). The appropriate HA/EDC/NHS-crosslinking time for SF nanofibrous matrices was 24 hours. The strain performance of the as-crosslinked SF nanofibers increased with an increase in HA concentration, with the optimal HA concentration being 0.3% (w/v). Fourier transform infrared spectroscopy analysis suggested that the HA/EDC/NHS-crosslinking process involves covalent reactions. The hydrophilicity of the SF nanofibrous matrices also increased with the addition of HA, which can be useful when trying to resist non-specific protein adsorption. In addition, the as-crosslinked SF nanofibrous matrices exhibited good cytocompatibility as shown by the cell viability data. Our work demonstrated that HA/EDC/NHS-crosslinking is a good choice for improving the tensile properties of the green electrospun SF nanofibers serving as skin tissue engineering scaffolds.